مسعود قمر کی نظم میں وجودی بیگانگی - Dr Sumaira Akbar; Dr Rabia Sarfaraz; Dr Abdul Aziz Malik (Khayaban - خیابان, 2022)
ABSTRACT: Masood Qamar is poet of modern Urdu poem. Two anthologies of his poems are published. His poetry influenced by existentialism. Existentialism a philosophical theory or approach which emphasizes the existence of the individual person as a free and responsible agent, determining their own development through acts of ones will. In the modern industrial age man has experienced himself as an alien. He has become not only alien to society but also estranged from himself. This attitude gives birth to isolation, Insane, suicide, death and abstraction. All these phenomena's are prominent features of Masood Qamar poetry. In this article ,effort is made to discover the above mentioned features in his poetry.